Towards an Ontology for User Activities on Smart Environments - Nascimento, Leonardo Vianna do; Oliveira, José Palazzo Moreira de (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2024.241224, 2024)
Most applications in smart environments must obtain data about their users and represent them (their context). One of the problems to be addressed in this domain is the user context representation. One of the main categories of context information in smart environments is user activity. This paper presents a mapping of the recent literature corresponding to human activity modeling using ontologies. Based on the results of this analysis, this work presents an ontology for representing human activities in smart spaces called ActivEOn. This ontology contains a high-level modeling of activities and related concepts that can be extended for specific domains. Two case studies using Protégé software demonstrated the developed ontology's potential.